Rasch‐built Overall Disability Scale for Multifocal motor neuropathy (MMN‐RODS©). Issue 3 (September 2015) - Vanhoutte, Els K.; Faber, Catharina G.; van Nes, Sonja I.; Cats, Elisabeth A.; Van der Pol, W.-Ludo; Gorson, Kenneth C.; van Doorn, Pieter A.; Cornblath, David R.; van den Berg, Leonard H.; Merkies, Ingemar S. J.; on behalf of the PeriNomS Study Group; Barreira, A.A.; et al.
Abstract Clinical trials in multifocal motor neuropathy (MMN) have often used ordinal‐based measures that may not accurately capture changes. We aimed to construct a disability interval outcome measure specifically for MMN using the Rasch model and to examine its clinimetric properties. A total of 146 preliminary activity and participation items were assessed twice (reliability studies) in 96 clinically stable MMN patients. These patients also assessed the ordinal‐based overall disability sum score (construct, sample‐dependent validity). The final Rasch‐built overall disability scale for MMN (MMN‐RODS©) was serially applied in 26 patients with newly diagnosed or relapsing MMN, treated with intravenous immunoglobulin (IVIg) (1‐year follow‐up; responsiveness study). The magnitude of change for each patient was calculated using the minimum clinically important difference technique related to the individually obtained standard errors. A total of 121 items not fulfilling Rasch requirements were removed. The final 25‐item MMN‐RODS© fulfilled all Rasch model's expectations and showed acceptable reliability and validity including good discriminatory capacity. Most serially examined patients improved, but its magnitude was low, reflecting poor responsiveness. The constructed MMN‐RODS© is a disease‐specific, interval measure to detect activity limitations in patients with MMN and overcomes the shortcomings of ordinal scales. However, future clinimetric studies are needed to improve the MMN‐RODS©'s responsiveness by longer observations and/or more rigorous treatment regimens.